Altered Basal Autophagy Affects Extracellular Vesicle Release in Cells of Lagotto Romagnolo Dogs With a Variant ATG4D - Syrjä P; Palviainen M; Jokinen T; Kyostila K; Lohi H; Roosje P; Anderegg L; Leeb T; Sukura A; Eskelinen EL (SAGE PUBLICATIONS INC, 2025)
Lagotto Romagnolo breed dogs develop a progressive neurological disease with intracellular vacuolar storage when homozygous for a variant in the autophagy-related gene 4D (ATG4D). A lysosomal enzyme deficiency has not been proven in this disease, despite its overlapping morphology with lysosomal storage diseases. Instead, basal autophagy was altered in fibroblasts from affected dogs. The aim of this study was to clarify the origin of the limiting membrane of the accumulating vacuoles and determine whether altered basal autophagy affects the extracellular release of vesicles in cells from diseased dogs. When assessed by immunoelectron microscopy, the membrane of the cytoplasmic vacuoles in affected tissues contained ATG4D, markers for autolysosomes (microtubule-associated protein 1A/B light chain 3 and lysosome-associated membrane protein 2) and for recycling endosomes (transferrin receptor 2), indicating that the vacuoles are hybrid organelles between endocytic and autophagic pathways. Ultracentrifugation, nanoparticle tracking analysis, and mass spectrometry were used to analyze the vesicles released from cultured fibroblasts of affected and control dogs. The amount of extracellular vesicles (EVs) released from affected fibroblasts was significantly increased during basal conditions in comparison to controls. This difference disappeared during starvation. The basal EV proteome of affected cells was enriched with cytosolic, endoplasmic reticulum, and mitochondrial proteins. Heat shock proteins and chaperones, some of which are known substrates of basal autophagy, were identified among the proteins unique to EVs of affected cells. An increased release of extracellular vesicles may serve as a compensatory mechanism in disposal of intracellular proteins during dysfunctional basal autophagy in this spontaneous disease.